Integrating Distance Education into Mobile Devices Using Adobe Connect Pro - Dian Luthfiyati; Oikurema Purwati; Widyastuti Widyastuti; Ahmad Munir (AL-ISHLAH: Jurnal Pendidikan, 2023)
This article aims to promote Adobe Connect Pro on online learning as a discussion platform in an online class. Digitalization in higher education using digital learning platforms such as adobe connect pro is currently broadly used as educational media. In the research context, Adobe Connect Pro is utilized as a discussion platform in the online class. Digital learning Platform enables providers to deliver academic programs via digital learning platforms, facilitating communication and enabling knowledge preservation, selection, and distribution. Using a qualitative study, this article investigates how Adobe Connect Pro allows teacher trainers to collaborate by offering a forum for real-time reflection and debate on student-teacher video performance, which is a natural extension of a forum. The result of the observation shows that Adobe Acrobat Connect Pro’s online discussion forum promotes students’ learning interests and accommodates a variety of learners, including those with special needs who may find it challenging to be physically present in the traditional classroom all of the time or to keep up with the other students. It promotes inclusive learning by allowing anyone to learn at their own pace and schedule and freely participate in platform discussions. In conclusion, discussion forums using Adobe Acrobat Connect Pro have immense potential to push students to learn.